ASSOCIATION OF SERUM HOMOCYSTEINE LEVELS WITH UNEXPLAINED STILL BIRTHS - Suman, Akanksha; Sinha, Dr. Sangeeta; Singh, Dr Sunita (Student's Journal of Health Research Africa, 2023)
Background This study examines the concept that elevated homocysteine levels are associated with sudden infant death syndrome. The study aimed to determine whether elevated serum homocysteine levels were related to an increased risk of iatrogenic stillbirths. Method In this retrospective case-control study, 100 women who had stillbirths for unknown reasons and 100 who had normal pregnancies served as cases and controls, respectively. The serum homocysteine levels were evaluated using enzyme assays, and other pertinent clinical and demographic information was also gathered. Result Significantly differing homocysteine levels were found between the case group (mean ± standard deviation: 12.5 ±2.1 units) and the control group (mean± standard deviation: 8.3± 1.5 units; p0.001). After adjusting for potential confounding factors Conclusion The results suggest that elevated serum homocysteine levels may be a biomarker for the unknown risk of stillbirth in women. Further research is required into potential treatments and prevention strategies for hyperhomocysteinemia-related pregnancy complications. This study supports the theory that elevated homocysteine levels induce sudden infant death syndrome. Significant therapeutic implications result from these findings, as systematic homocysteine monitoring throughout pregnancy may help identify high-risk patients and implement appropriate therapies to reduce stillbirths. Recommendation There is a need for additional research to validate these findings and investigate methods to reduce maternal homocysteine levels such as maternal age, smoking status, and gestational age, logistic regression analysis revealed an important association between elevated serum homocysteine levels and unexplained stillbirths (odds ratio: 2.90, 95% confidence interval: 1.70-4